2019
DOI: 10.1007/s10208-018-09407-7
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Analysis of Deterministic Kernel-Based Quadrature Rules in Misspecified Settings

Abstract: This paper presents convergence analysis of kernel-based quadrature rules in misspecified settings, focusing on deterministic quadrature in Sobolev spaces. In particular, we deal with misspecified settings where a test integrand is less smooth than a Sobolev RKHS based on which a quadrature rule is constructed. We provide convergence guarantees based on two different assumptions on a quadrature rule: one on quadrature weights, and the other on design points. More precisely, we show that convergence rates can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 47 publications
3
58
0
Order By: Relevance
“…See [63,Corollary 11.33] or [64,Proposition 3.6] for earlier and slightly more restricted results that require r > d/2 and [29, Proposition 4] for a version specifically for numerical integration. Some assumptions, satisfied by all domains of interest to us, are needed; see for instance [29,Section 3] for precise definitions. This assumption essentially says that the boundary of Ω is sufficiently regular (Lipschitz boundary) and that there is no "pinch point" on the boundary of Ω (interior cone condition).…”
Section: Kernels Inducing Sobolev-equivalent Rkhssmentioning
confidence: 99%
See 2 more Smart Citations
“…See [63,Corollary 11.33] or [64,Proposition 3.6] for earlier and slightly more restricted results that require r > d/2 and [29, Proposition 4] for a version specifically for numerical integration. Some assumptions, satisfied by all domains of interest to us, are needed; see for instance [29,Section 3] for precise definitions. This assumption essentially says that the boundary of Ω is sufficiently regular (Lipschitz boundary) and that there is no "pinch point" on the boundary of Ω (interior cone condition).…”
Section: Kernels Inducing Sobolev-equivalent Rkhssmentioning
confidence: 99%
“…One of our principal aims is to stimulate new research on quadrature weights in the context of probabilistic numerics. While convergence rates of Bayesian quadrature rules have been studied extensively in recent years [10,28,29], analysis of the weights themselves has not attracted much attention. On the other hand, the earliest work [36,55,3] (see [44] for a recent review) done in the 1970s on kernel-based quadrature already revealed certain interesting properties of the Bayesian quadrature weights.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…as N → ∞ has been studied in both the well-specified [4,60,7,19,8] and mis-specified [28,29] regimes. Some relationships between the posterior mean estimator and classical cubature methods have been documented in [16,56,30].…”
Section: Introductionmentioning
confidence: 99%
“…The mean (green; Equation(29)) and maximal (red; Equation (30)) relative integration errors obtained when simultaneously approximating D global illumination integrals (28) using Bayesian cubature (BC) with random points and fully symmetric multi-output Bayesian cubature (MOBC). Here J = 3 and J = 6 random generator vectors were used to produce a fully symmetric point set of size N = 144 (for J = 3) and N = 288 (for J = 6).…”
mentioning
confidence: 99%